Comprehension Monitoring Strategies for Fostering Reading Comprehension - LARABA, Samir (Journal of Human Sciences, 2012)
The present article investigates the effects of comprehension monitoring strategies on performance in reading comprehension. The monitoring techniques opted for are coding texts, restating, asking questions, thinking aloud and repair strategies. Particular attention is given to this subject matter because reading is the language skill most widely practiced in the academic context, and thus success with reading comprehension is of paramount importance for learners. Comprehension, however, is not taught as such; it is rather tested via some questions that follow the reading of a given text. Therein lays the need for finding the instructional methods which can best assist learners in improving their text understanding.